Financial Literacy Empowerment in the Stock Market - Saeedi, Ali (Springer International Publishing, 2018)
This book provides an overview of current issues associated to financial literacy improvement. In selecting and structuring the material to include, the primary criterion has been applicability of topics and recommendations and accuracy of trends toward better financial literacy level. Each chapter is dedicated to a particular component of financial literacy from education to capability. Throughout the book, there are many practices initiated around the world which, regardless of their superiority, are all useful initiatives and can roll play as a spot light in the road of improvement for both investors and authorities. This book is not only applicable for academics and students, but authorities who aim to improve financial literacy (and subsequently financial capability) among individuals and for those investors who seek to improve their own financial literacy.